ASSESSMENT OF RISK OF DEVELOPMENT OF THROMBO-HEMORRHAGIC COMPLICATIONS IN OBSTETRICS USING A PREDICTIVE COEFFICIENT KULBACK AND BAYES' THEOREM - Tatiana Petrovna Bondar; Elena Olegovna Melikbekyan (Наука. Инновации. Технологии)
A current study on developing a method of assessing the risk of thrombo-hemorrhagic complications in pregnant women with a prognostic factor Kulback and Bayes' theorem. We studied platelet hemostasis parameters in women with physiological pregnancy and in women in the presence of thrombo-hemorrhagic complications, as well as evaluated the frequency of the studied parameters in healthy mothers and postpartum women with disorders of the hemo-static system. It was revealed that the study of morphological, quantitative and functional parameters of platelet and statistical processing of the data by a factor Kulback and Bayes' theorem it is advisable to identify the risk of thrombogenic complications.